67th Merdeka Celebration: the unique features of the Malaysian society - Abdul Razak, Mohd Abbas; Mustapha, Maziah (Department of Communication, KIRKHS, IIUM, 2024)
This short article is written in conjunction with the 67th Merdeka Day celebration. The theme for this year’s celebration is ‘Malaysia Madani: Jiwa Merdeka’ which translates to ‘Civilized Malaysia: Free Spirit.’ In civilized Malaysia, people from all walks of life, including leaders and ordinary citizens, are expected to uphold good conduct, embodying the essential qualities of a responsible and ethical citizen. To progress as a nation and achieve greater heights of success, it is crucial to eradicate the culture of bribery, corruption, and misuse of power in every sector of our life as Malaysians. Embracing the spirit of freedom, every race in Malaysia should be treated with fairness and justice. The freedom to voice opinions is essential, but it must be exercised diplomatically underMalaysian ethics and adab. The right to speak the truth and seek justice must always be coupled with responsibility. This is not a call for unrestrained freedom, as seen in some parts of the world, but for freedom that respects the values and responsibilities inherent in our society. Every individual as God’s creation is unique. Similarly, every nation has its own uniqueness and attraction. Some advanced countries in the world are special for their great achievements in the areas of science and technology. Countries in the West that have enchanting landscapes become ideal spots for holidaymakers to enjoy time together with family and friends. In contrast, countries in the East that have interesting cuisines, warm weather and beautiful beaches attract a great volume of tourists from the rich and colder regions of the world. Malaysia has its own interesting characteristics that are different from those of many countries in the world. Malaysia got its sovereignty from the British colonial rule on 31st August 1957. It has a diverse population. Three main ethnic groups live in Malaysia, they are the Malays who are called ‘Bumiputeras’ or ‘Sons of the Soil’, the Chinese and Indians. In addition, many indigenous people live in the peninsular of Malaysia, Sabah and Sarawak (these two states are also called as East Malaysia). This year Malaysians will be celebrating the 67th Independence Day, popularly known as Hari Kemerdekaan. Annals of Malaysia say that, on the eve of Malaysia’s independence, many foreign political observers predicted that there would be racial and power struggles that would eventually fail the newly formed country. Directly opposite to the prediction, Malaysia managed to sail through for many decades after being liberated from the clutches of its colonial master. Between the years 1968 and 1989, the communist insurgency tried to grab power through the use of terror and violence, but it failed. At the moment, Communism is not a threat to Malaysia as it has been abolished in toto. Besides that, in 1969, Malaysia first experienced a racial clash threatening the unity established during its inception. Within three days, the local authorities managed to bring the clashes under control and successfully restored peace and order in the country. Malaysia, which began as an agrarian country, has successfully diversified its economy by venturing into science, technology, and industrialization. The nation and its people emphasize the importance of balance and moderation in all aspects of life. This philosophy is reflected in Malaysia’s approach to education and governance, where the values of moderation are upheld, and the needs of civil society are prioritized. The Malaysian government wants to become a fully developed nation in the next few decades. To do this, the government is working hard to reduce the differences between the various ethnic groups living in the country. These efforts are part of a bigger plan to create a united identity called ‘Bangsa Malaysia’ in the near future.